(untitled) (International Journal of Agriculture and Sustainable Development, 2022)
Herbs and spices, which are aromatic plants, have been used for food preservation and traditional medicine since ancient times. Oregano, rosemary, sage, anise, basil, and many other well-known aromatic herbs have their roots in the Mediterranean. Antimicrobial, antioxidant, antiparasitic, antiprotozoal, antifungal, and anti-inflammatory properties have all been observed in these plants because of the high concentration of polyphenolic compounds they contain. Increased interest in these plants and their derivatives can be attributed to the fact that they are all-natural, environmentally friendly, and widely acknowledged to be safe. This means that aromatic plants and their extracts could play a role in the next generation of substances used to improve human and animal health through diet and supplementation. The goal of this article is to provide a synopsis of the research on aromatic plants’ in vivo and in vitro applications.